Trends in Childhood Poison Exposures and Fatalities: A Retrospective Secondary Data Analysis of the 2009-2019 U.S. National Poison Data System Annual Reports - Hong Li; Teresa Dodd-Butera; Margaret L. Beaman; Molly Broderick Pritty; Thomas E. Heitritter; Richard F. Clark (MDPI AG, 2021)
Despite significant prevention efforts, childhood poison exposures remain a serious public health challenge in the United States. This study aimed to assess annual trends of pharmaceutical vs. non-pharmaceutical poison exposures in the US among children 0-19 years and compare the odds of death by children's age group. Poison exposure and fatality data were retrospectively extracted from 2009 to 2019 National Poison Data System (NPDS) annual reports for children in all reported age groups. Overall, there was a significant reduction in the annual population-adjusted poison exposures in children (annual percentage change = −2.54%, 95% CI = −3.94% to −1.15%, p < 0.01), but not in poisoning-related fatalities. Children 0-5 had similar odds of dying from exposure to non-pharmaceuticals vs. pharmaceuticals. The odds of children 6-12 dying from non-pharmaceuticals vs. pharmaceuticals was 2.38 (95% CI = 1.58, 3.58), χ2 = 18.53, p < 0.001. In contrast, the odds of children 13-19 dying from pharmaceuticals vs. non-pharmaceuticals was 3.04 (95% CI = 2.51, 3.69), χ2 = 141.16, p < 0.001. Suicidal intent accounted for 40.63% of pharmaceutical deaths in children 6-12, as well as 48.66% of pharmaceutical and 31.15% of non-pharmaceutical deaths in children 13-19. While a significant decline in overall childhood poison exposures was reported, a decrease in poisoning-related fatalities was not observed. Children in different age groups had contrasting relative odds of death from pharmaceutical and non-pharmaceutical exposures. Among older children, a greater proportion of poisoning-related deaths was due to intentional suicide. These findings provide evidence of age-specific trends in childhood poison exposure risk and directions for future poison prevention efforts and behavioral health partnerships.